Prevalence of Trachoma in Kogi State, Nigeria: Results of four Local Government Area-Level Surveys from the Global Trachoma Mapping Project - Alada, Joel J. (Ophthalmic Epidemiol, 2018)
Purpose: To determine the prevalence of trachoma in four Local Government Areas (LGAs) of Kogi State, Nigeria. Methods: In June 2014, we conducted population-based, cross-sectional surveys according to Global Trachoma Mapping Project (GTMP) protocols in selected LGAs of Kogi State. In each LGA, 25 clusters were selected with probability proportional to size. In each of these clusters, 25 households were enrolled for the survey. All residents of selected households aged ≥1 year were examined by GTMP-certified graders for trachomatous inflammation–follicular (TF) and trichiasis using the simplified trachoma grading scheme. Data on sources of household water and types of sanitation facilities were collected through questioning and direct observation. Results: The age-adjusted TF prevalence in 1–9-year-olds ranged from 0.4% (95% CI 0.1–0.8%) in Bassa to 1.0% (95% CI 0.3–1.9%) in Omala. Across all four LGAs, only one case of trichiasis was found; this individual was in Omala, giving that LGA a trichiasis prevalence in individuals aged ≥15 years of 0.02% (95% CI 0.00–0.07%). Between 77 and 88% of households had access to water for hygiene purposes, while only 10–30% had access to improved sanitation facilities. Conclusion: Trachoma is not a public health problem in any of the 4 LGAs surveyed. There is, however, the need to increase access to adequate water and sanitation services to contribute to the health and social and economic well-being of these communities.